CD3ε Expression Defines Functionally Distinct Subsets of Vδ1 T Cells in Patients With Human Immunodeficiency Virus Infection - Dunne, Pádraic J.; Maher, Christina O.; Freeley, Michael; Dunne, Katie; Petrasca, Andreea; Orikiiriza, Judy; Dunne, Margaret R.; Reidy, Derval; O’Dea, Siobhan; Loy, Aisling; Woo, Jim; Long, Aideen; et al. (Frontiers in Immunology, 2018)
Human γδ T cells expressing the Vδ1 T cell receptor (TCR) recognize self and microbial antigens and stress-inducible molecules in a major histocompatibility complex -unrestricted manner and are an important source of innate interleukin-17. Vδ1 T cells are expanded in the circulation and intestines of patients with human immunodeficiency virus (HIV) infection. In the present study, we show that patients with HIV have elevated frequencies, but not absolute numbers, of circulating Vδ1 T cells compared to control subjects. This increase was most striking in the patients with Candida albicans co-infection. Using flow cytometry and confocal microscopy, we identify two populations of Vδ1 T cells, based on low and high expression of the ε chain of the CD3 protein complex responsible for transducing TCR-mediated signals (denoted CD3εlo and CD3εhi Vδ1 T cells). Both Vδ1 T cell populations expressed the CD3 ζ-chain, also used for TCR signaling. Using lines of Vδ1 T cells generated from healthy donors, we show that CD3ε can be transiently downregulated by activation but that its expression is restored over time in culture in the presence of exogenous interleukin-2. Compared to CD3εhi Vδ1 T cells, CD3εlo Vδ1 T cells more frequently expressed terminally differentiated phenotypes and the negative regulator of T cell activation, programmed death-1 (PD-1), but not lymphocyte activation gene 3 (LAG-3), and upon stimulation in vitro, only the CD3εhi subset of Vδ1 T cells, produced interleukin-17. Thus, while HIV can infect and kill IL-17-producing CD4+ T cells, Vδ1 T cells are another source of IL-17, but many of them exist in a state of exhaustion, mediated either by the induction of PD-1 or by downregulation of CD3ε expression.